INTERNATIONAL COMMUNITY SERVICE THROUGH SME BUSINESS DIAGNOSTICS: CUSTOMER-ORIENTED STRATEGY FOR A COFFEE AND SNACK SHOP IN KUALA LUMPUR - Iwan Kresna Setiadi; Ivan Yulivan; Yudi Nur Supriadi; Reza Palevi Alren; Syakir Abdul Wadud; Zackharia Rialmi (Batara Wisnu : Indonesian Journal of Community Services, 2026)
International community service can connect academic knowledge with the immediate needs of micro, small, and medium enterprises (MSMEs) operating in multicultural urban settings. This article reports a Corporate Social Innovation (CSI) activity conducted by a team from Universitas Pembangunan Nasional “Veteran” Jakarta in collaboration with Universiti Kuala Lumpur at a coffee and snack shop in the lobby of Regalia Residence, Kuala Lumpur, Malaysia. The activity aimed to identify the partner’s operational and marketing challenges, interpret customer-behavior patterns, and formulate feasible customer-oriented recommendations. A participatory business-diagnostic approach was applied through pre-visit desk research, a one-day field visit, direct observation, semi-structured conversations with the owner and staff, informal customer interactions, photographic documentation, and thematic analysis. The diagnostic process identified four interrelated issues: dependence on fluctuating lobby traffic, the need to serve both residents and short-stay visitors, limited differentiation in a competitive food-and-beverage environment, and underutilized customer-retention and digital-promotion opportunities. The service team translated these findings into a practical strategy package comprising time-based menu planning, a simple loyalty mechanism, low-cost digital content, distinctive menu development, and collaboration with residence management. The principal output was a context-specific set of recommendations and a shared understanding of the shop’s market position; however, the short engagement did not permit measurement of post-implementation business outcomes. The activity demonstrates that international community service can create reciprocal learning and actionable value when recommendations are grounded in partner dialogue, local observation, and realistic resource constraints